A novel RGDyC/PEG co-modified PAMAM dendrimer-loaded arsenic trioxide of glioma targeting delivery system - Lu Y (International Journal of Nanomedicine, 2018)
Yanping Lu,1 Shunping Han,1 Hongyue Zheng,1 Rui Ma,1 Yuting Ping,1 Jiafeng Zou,1 Hongxia Tang,1 Yongping Zhang,2 Xiuling Xu,1 Fanzhu Li1 1College of Pharmaceutical Sciences, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, China; 2College of Pharmaceutical Sciences, Guiyang University of Chinese Medicine, Guiyang, Guizhou, China Background: The Traditional Chinese Medicine, arsenic trioxide (ATO, As2O3) could inhibit growth and induce apoptosis in a variety of solid tumor cells, but it is severely limited in the treatment of glioma due to its poor BBB penetration and nonspecifcity distribution in vivo. Purpose: The objective of this study was encapsulating ATO in the modified PAMAM dendrimers to solve the problem that the poor antitumor effect of ATO to glioma, which provide a novel angle for the study of glioma treatment. Methods: The targeting drug carrier (RGDyC-mPEG-PAMAM) was synthesized based on Arg-Gly-Asp (RGDyC) and αvβ3 integrin targeting ligand, and conjugated to PEGylated fifth generation polyamidoamine dendrimer (mPEG-PAMAM). It was characterized by nuclear magnetic resonance, fourier transform infrared spectra, Nano-particle size-zeta potential analyzer,etc. The in vitro release characteristics were studied by dialysis bag method. MTT assay was used to investigate the cytotoxicity of carriers and the antitumor effect of ATO formulation. In vitro blood-brain barrier (BBB) and C6 cell co-culture models were established to investigate the inhibitory effect of different ATO formulation after transporting across BBB. Pharmacokinetic and antitumor efficacy studies were investigated in an orthotopic murine model of C6 glioma. Results: The prepared RGDyC-mPEG-PAMAM was characterized for spherical dendrites, comparable size (21.60±6.81 nm), and zeta potential (5.36±0.22 mV). In vitro release showed that more ATO was released from RGDyC-mPEG-PAMAM/ATO (79.5%) at pH 5.5 than that of pH 7.4, during 48 hours. The cytotoxicity of PEG-modified carriers was lower than that of the naked PAMAM on both human brain microvascular endothelial cells and C6 cells. In in vitro BBB model, modification of RGDyC heightened the cytotoxicity of ATO loaded on PAMAM, due to an increased uptake by C6 cells. The results of cell cycle and apoptosis analysis revealed that RGDyC-mPEG-PAMAM/ATO arrested the cell cycle in G2-M and exhibited threefold increase in percentage of apoptosis to that in the PEG-PAMAM/ATO group. Compared with ATO-sol group, both RGDyC-mPEG-PAMAM/ATO and mPEG-PAMAM/ATO groups prolonged the half-life time, increased area under the curve, and improved antitumor effect, significantly. While the tumor volume inhibitory of RGDyC-mPEG-PAMAM/ATO was 61.46±12.26%, it was approximately fourfold higher than the ATO-sol group, and twofold to the mPEG-PAMAM/ATO group. Conclusion: In this report, RGDyC-mPEG-PAMAM could enhance the antitumor of ATO to glioma, it provides a desirable strategy for targeted therapy of glioma. Keywords: arsenic trioxide, blood-brain barrier, RGDyC, PEG co-modified, glioma targeting delivery, PAMAM dendrimer